Caracterização do viroma de animais e plantas através da análise do padrão e sequência de pequenos RNAs produzidos pela resposta do hospedeiro - Eric Roberto Guimarães Rocha Aguiar (2015)
Surveillance of pool of virus, Virome, present in environmental samples are important to biodiversity studies and can greatly help to human and veterinary health. The virome of vector insects have special interest to public health authorities. Metagenomic from largescale sequencing of small and long RNAs have been used to detect viruses, althoughadvantages and disadvantages of each one have not been analyzed. Furthermore, the identification of viral sequences is limited by similarity searches against reference databases. Here, we developed a strategy to detect virus from small RNA libraries that take advantage of not only sequence similarity searches against reference database butalso a sequence-independent strategy. This method relies on the production of virusderived small RNAs by the host response such as the RNA interference pathway. Using this strategy, we identify 7 viruses, from which six likely represents new species that compose the virome of laboratory populations of fruit flies and two insect vectors, mosquitoes and sandflies. In Aedes, we compared sequencing of small and long RNAs and reveal that viral sequences are enriched in the small RNA fraction. We also noted that the small RNA size profile was a unique signature of each virus and could be used to identify novel viral sequences without known relatives in reference databases.Furthermore, we show that the small RNA profile could be used to infer viral tropism for ovaries among other aspects of virus biology. Additionally, we applied this strategy to individual mosquitoes caught directly from field where we identified 3 viruses, which twoof them have been previously identified in Aedes aegypti laboratory populations, Phasi Charoen-like virus (PCLV) and Humaita-Tubiacanga virus (HTV), and the third, Mosquito caratinga virus (MCV), likely representing a new specie. However, while PCLV and HTV where found circulating in individual mosquitoes in all seasons, MCV was restricted tosummer. The high prevalence of PCLV and HTV suggests those viruses are component of resident virome of wild mosquitoes while MCV would be a transient component. Regarding the application of our strategy, we showed that virus detection utilizing small RNAs could be applied to vertebrate animals although not as efficiently as to plants and insects.